2020
DOI: 10.1111/1471-0528.16377
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality for acute pain in outpatient hysteroscopy: a randomised controlled trial

Abstract: Objective To evaluate the effectiveness of virtual reality as a distraction technique in the management of acute pain and anxiety during outpatient hysteroscopy. Design Parallel group, prospective randomised controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 38 publications
(68 reference statements)
1
35
1
1
Order By: Relevance
“…We have read with interest the study by Deo et al published in BJOG: An International Journal of Obstetrics and Gynaecology. 1 We noted that although the control and the virtual reality (VR) group were 'comparable' regarding previous hysteroscopies, differences in baseline pain expectation scores between patients with a previous hysteroscopy and patients without previous hysteroscopy were not given. Each patient has an individual pain experience during hysteroscopy: some may not experience any pain at all, whereas others feel pain during cervical manipulation, distension of the uterus or pipelle biopsy, or delayed pain as a result of the release of prostaglandins.…”
Section: Sirmentioning
confidence: 98%
“…We have read with interest the study by Deo et al published in BJOG: An International Journal of Obstetrics and Gynaecology. 1 We noted that although the control and the virtual reality (VR) group were 'comparable' regarding previous hysteroscopies, differences in baseline pain expectation scores between patients with a previous hysteroscopy and patients without previous hysteroscopy were not given. Each patient has an individual pain experience during hysteroscopy: some may not experience any pain at all, whereas others feel pain during cervical manipulation, distension of the uterus or pipelle biopsy, or delayed pain as a result of the release of prostaglandins.…”
Section: Sirmentioning
confidence: 98%
“…It is a computer-generated representation of an immersive environment viewed through a headset. VR is effective in reducing pain and anxiety during outpatient hysteroscopy [19].…”
Section: Virtual Realitymentioning
confidence: 99%
“…In a non-randomized controlled study recruiting patients undergoing colposcopy (cervical examination), Vasquez et al showed that patients assigned to VR group reported reduced pain scores post-VR intervention [20]. Another prospective randomized controlled trial in an outpatient hysteroscopy setting showed that the use of VR during the procedure resulted in significantly decreased average pain score and anxiety when compared to controls [21]. Nevertheless, there are limited studies conducted in a gynecological population, and no formal sample size calculations were performed to study the expected clinical effect size related to pre-operative anxiety.…”
Section: Introductionmentioning
confidence: 99%